Introducing artificial intelligence in Chinese agriculture (review) - E. G. Raevskaya (Аграрная наука Евро-Северо-Востока, 2024)
In recent years, significant breakthroughs are observed in developing artificial intelligence (AI), which radically affects the most diverse areas of human life and activity. This review article examines the introduction of AI in agriculture using the example of China, which is a leader in the pace of introduction of AI into the national economy and seeks to head off the United States in the overall leadership in the development of AI technologies. Thanks to active work in this direction and significant financial investments in this area, China has managed to transform substantially its agricultural sector.  The purpose of the article is to analyze the current trends and opportunities offered by the application of AI in the agricultural sector of the PRC economy. To this end, a series of difficulties that China faces in the development of agriculture is considered, as well as the main currently known areas of application of AI in agriculture and the types of technologies used. Information on Chinese companies using AI technologies in agriculture is summarized, including their specialization, technologies used and benefits gained. Early evidence shows that AI is being applied firstly to improve productivity and manufacturing performance, and secondly to address labor shortages and achieve manufacturing sustainability. Analysis of the situation allows  us to conclude that AI can become the main driving force in the development of agriculture.